It’s Time for Some “Site”-Seeing: Novel Tools to Monitor the Ubiquitin Landscape in Arabidopsis thaliana - Walton, Alan (Plant Cell, 2016)
Ubiquitination, the covalent binding of the small protein modifier ubiquitin to a target protein, is an important and frequently studied posttranslational protein modification. Multiple reports provide useful insights into the plant ubiquitinome, but mostly at the protein level without comprehensive site identification. Here, we implemented ubiquitin combined fractional diagonal chromatography (COFRADIC) for proteome-wide ubiquitination site mapping on Arabidopsis thaliana cell cultures. We identified 3009 sites on 1607 proteins, thereby greatly increasing the number of known ubiquitination sites in this model plant. Finally, The Ubiquitination Site tool (http://bioinformatics.psb.ugent.be/webtools/ubiquitin_viewer/) gives access to the obtained ubiquitination sites, not only to consult the ubiquitination status of a given protein, but also to conduct intricate experiments aiming to study the roles of specific ubiquitination events. Together with the antibodies recognizing the ubiquitin remnant motif, ubiquitin COFRADIC represents a powerful tool to resolve the ubiquitination maps of numerous cellular processes in plants.